2015
DOI: 10.1161/hypertensionaha.115.05674
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Mineralocorticoid Receptor Blockade Prevents Western Diet–Induced Arterial Stiffening in Female Mice

Abstract: Women are especially predisposed to development of arterial stiffening secondary to obesity due to consumption of excessive calories. Enhanced activation of vascular mineralocorticoid receptors impairs insulin signaling, induces oxidative stress, inflammation and maladaptive immune responses. We tested whether a sub-pressor dose of mineralocorticoid receptor antagonist, spironolactone (1 mg•kg−1•day−1) prevents aortic and femoral artery stiffening in female C57BL/6J mice fed a high fat/high sugar western diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
171
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(190 citation statements)
references
References 44 publications
(48 reference statements)
16
171
2
Order By: Relevance
“…28 Similar results were obtained in wild-type mice that received high-fat diet. 5 In line with this, high-fat diet-induced endothelial dysfunction and impaired vascular relaxation was restored by endothelial MR deletion. 1,6 This was accompanied by reduced oxidative stress and improved nitric oxide production in EC-MRKO mice 1,6 or after spironolactone treatment.…”
Section: Vascular Stiffness Dysfunction and Blood Pressure Regulationsupporting
confidence: 55%
See 1 more Smart Citation
“…28 Similar results were obtained in wild-type mice that received high-fat diet. 5 In line with this, high-fat diet-induced endothelial dysfunction and impaired vascular relaxation was restored by endothelial MR deletion. 1,6 This was accompanied by reduced oxidative stress and improved nitric oxide production in EC-MRKO mice 1,6 or after spironolactone treatment.…”
Section: Vascular Stiffness Dysfunction and Blood Pressure Regulationsupporting
confidence: 55%
“…1,6 This was accompanied by reduced oxidative stress and improved nitric oxide production in EC-MRKO mice 1,6 or after spironolactone treatment. 5 It has been demonstrated that ENaC is also expressed outside of the kidney in endothelial cells and contributes to endothelial cell and vascular stiffness. 29,30 ENaC expression increases with age or in response to high-fat diet.…”
Section: Vascular Stiffness Dysfunction and Blood Pressure Regulationmentioning
confidence: 99%
“…In a mouse model of Western diet‐induced obesity, females developed higher plasma aldosterone levels compared with males 25. MR blockade in rodents improved endothelial function in females more than males in the setting of diabetes mellitus or hyperleptinemia—common complications of obesity 26, 27. These studies support a potential role for MR in endothelial dysfunction induced by cardiometabolic risk factors and suggest that the role of MR may be enhanced in females.…”
Section: Introductionmentioning
confidence: 64%
“…Because aldosterone excess per-se has been linked to multiple potential unfavorable sequels, such as the evolution of hypertension, 25 cardiac and vascular fibrosis, 26,27 insulin resistance, 28 and worse prognosis after myocardial infarction, 29 the present report should instigate further studies of whether/how this previously unrecognized inhibitor of aldosterone secretion can be used under conditions in which high circulating aldosterone is a likely contributor to disease.…”
Section: Perspectivesmentioning
confidence: 96%